Analisis Pembentukan Akhlak Anak Melalui Media Sosial pada Siswa Kelas 1 di MI/SD - Muzfirah, Suci; Zahra, Fatimatuz; Febiana, Novi; Jannah, Uzlifatul (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Social media is a social structure that comes from individuals and organizations that are bound by the similarity of its users. Social media is an online media that is used as a means of social interaction online on the internet. On social media, users can interact with each other, communicate, share networking and various other activities online. Social media is made to meet human requirements because humans as social beings, are created to socialize. Because the development of the era is increasingly advanced, the main purpose of which is to facilitate users of social media so that they can connect with someone in one country, even between countries or between continents, making it easy for users to socialize. However, in today's modern era, social media does not only function as usual, it turns out that social media has influences on the character education of students who use it. Talking about strengthening the formation of student character through character education in the current context is very relevant to overcoming the moral crisis that is happening, especially in schools. Whether it is recognized or not, there is currently a real crisis that is worrying in the school environment involving students.